Game Edukasi Pengenalan Gaya Gesek Pada Materi Fisika Siswa SMA - Muhammad Luthfi Pratama; Nenna Irsa Syahputri; Nur Wulan (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
Computer technology is one that is growing rapidly at this time, one of its impacts can be seen in the world of education. In every era of education there are always changes that lead to better progress. The world of education requires various changes and innovations for the sake of advancing the quality of education that does not focus on theory only, but also on practical matters. For the current COVID-19 pandemic, the teaching and learning process is carried out online or online from home. This can cause a problem, namely a lack of interest and interest in learning for students to take part in learning due to the lack of interaction between students and teachers. Therefore, a new learning method and an alternative learning method were created, namely by making an educational game. Here, the researcher makes an educational game introducing the friction force in physics by using a software called Adobe Flash CS6 and also using the ActionScript 3.0 programming language. A game is made that contains learning materials and also a game that has two styles of play, the first is a brain teaser game and the second is an essay test game. The brain teaser play model is in the form of multiple choice by being given several choices to answer, and the essay test playing model is in the form of a game of filling in answers in the column by being given a grid of questions to answer questions. It is hoped that with this educational game, teachers can be helped in providing more understanding to students, and can also help increase student interest in learning